Economy And Covid as A Reflexivity of Islam Science Language at Plural Worship With R12-R47 Methodology - Aziz, R Mochamad (Universitas Muhammadiyah Surakarta, 2021)
Purpose: The study has objection to analyzing the existence of economy and Covid with the reflexivity model as R12 to science and language as Islamic structure by R47 methodology. R12 is a simple constant at the beginning of creation. R47 is a complex structure of a physical object in existing creation. Methodology: These research objects are reflexivity of religion to science as the economy and Covid and sentence of the holy book. The study worked out through books, journals, holy books, and other electronic media. The methodology uses descriptive analytics with similarities and comparative sentences in language grammar. The methods are reflexivity, parallel, and hahslm 472319. Results: The results are the analogy of R-12 as worship of Plural Pray (Salat Jamak) before R-47. R-47 is the physical connection as the existing creation in-universe. The comparative sentence between ‘Not I create jin and human except for worship’ with ‘Not I create tea and coffee except for guest’. Applications/Originality/Value: The blueprint presence is reflexivity of the constant 12 stored from the Quran 51.56 verse number (1+5) times (5+6) root of digit 2 becomes 6x2=12. Twelve reflects 1 salat Subuh and 2 salat Jamak (Dzuhur Asar and Magrib Isa). R-12 can be illustrated as religion and R-47 can be illustrated as science where R-12 simple is the same with R-12* complex or R-47. This R-12 and R-47 also can be adapted to languages structures in economic covid age.